Identification of conserved core xylem gene sets: conifer cDNA microarray development, transcript profiling and computational analyses. - Pavy, N; Boyle, B; Nelson, C; Paule, C; Giguère, I; Caron, S; Parsons, L; Dallaire, N; Bedon, F; Bérubé, H; Cooke, J; Mackay, J (2008)
One approach for investigating the molecular basis of wood formation is to integrate microarray profiling data sets and sequence analyses, comparing tree species with model plants such as Arabidopsis. Conifers may be included in comparative studies thanks to large-scale expressed sequence tag (EST) analyses, which enable the development of cDNA microarrays with very significant genome coverage. A microarray of 10,400 low-redundancy sequences was designed starting from white spruce (Picea glauca (Moench.) Voss) cDNAs. Computational procedures that were developed to ensure broad transcriptome coverage and efficient PCR amplification were used to select cDNA clones, which were re-sequenced in the microarray manufacture process. White spruce transcript profiling experiments that compared secondary xylem to phloem and needles identified 360 xylem-preferential gene sequences. The functional annotations of all differentially expressed sequences were highly consistent with the results of similar analyses carried out in angiosperm trees and herbaceous plants. Computational analyses comparing the spruce microarray sequences and core xylem gene sets from Arabidopsis identified 31 transcripts that were highly conserved in angiosperms and gymnosperms, in terms of both sequence and xylem expression. Several other spruce sequences have not previously been linked to xylem differentiation (including genes encoding TUBBY-like domain proteins (TLPs) and a gibberellin insensitive (gai) gene sequence) or were shown to encode proteins of unknown function encompassing diverse conserved domains of unknown function.